2011
DOI: 10.1111/j.1365-3016.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of preterm delivery and hypertensive disorders of pregnancy in relation to maternal co‐morbid mood and migraine disorders during pregnancy

Abstract: Summary We evaluated risks of preterm delivery and hypertensive disorders of pregnancy among pregnant women with mood and migraine disorders. We used data from a cohort study of 3,432 pregnant women. Maternal pre-gestational or early pregnancy (before 20 weeks gestational) mood disorder and pre-gestational migraine diagnoses were ascertained from in-person interview and medical record review. We fitted generalized linear models to derive risk ratios (RR) and 95% confidence intervals (CI) of preterm delivery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 36 publications
5
73
2
1
Order By: Relevance
“…For example, women from low SES backgrounds and those who are unmarried (not living with a partner) appear to be more likely to experience maternal health conditions in pregnancy, which may contribute to their increased risk of delivering lower birth weight and/or lower gestational age infants. [54][55][56][57][58][59] The presence of significant effects here by both social disadvantage and health conditions in pregnancy reflect this dual layering of stress sources and the adverse implications for birth outcomes. As noted, cumulative stress models point to dysregulatory cascades across physiological systems, transferring effects of stress to birth outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, women from low SES backgrounds and those who are unmarried (not living with a partner) appear to be more likely to experience maternal health conditions in pregnancy, which may contribute to their increased risk of delivering lower birth weight and/or lower gestational age infants. [54][55][56][57][58][59] The presence of significant effects here by both social disadvantage and health conditions in pregnancy reflect this dual layering of stress sources and the adverse implications for birth outcomes. As noted, cumulative stress models point to dysregulatory cascades across physiological systems, transferring effects of stress to birth outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…52,53 Studies have also shown that pregnancy-related health conditions and maternal health conditions in pregnancy contribute to an increased risk of adverse birth outcomes. [54][55][56][57][58][59] Using data from a prospective cohort study, we examined the pathways linking maternal social disadvantage to birth outcomes. Weathering theory posits that social disadvantage influences health outcomes through physical embodiment mechanisms as well as psychosocial and health behavior pathways.…”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately 15%-30% of women experience mood and anxiety disorders during pregnancy. 2,3 Self-reported symptoms of antenatal mood disorders are associated with risk behaviors (e.g., smoking 4 and substance use during pregnancy 5 ), pregnancy complications (e.g., preeclampsia 6,7,8 and low birth weight 9 ), and long term adverse outcomes in the mother (e.g. poor postpartum mental health 5 ) and her offspring (e.g.…”
mentioning
confidence: 99%
“…or siblings) [9,11]. It has been known that diabetes that occurs during pregnancy can have severe adverse effects on fetal and neonatal outcomes.…”
Section: International Journal Of Dental Sciences and Researchmentioning
confidence: 99%
“…Pregnancy has long been recognized as a state of relative insulin resistance, and those women who cannot meet the increased demands for insulin during pregnancy have been labeled as having gestational diabetes mellitus (GDM). [9] It occurs in about 2%-5% of all pregnancies and may improve or disappear after delivery. Gestational diabetes is fully treatable, but requires careful medical supervision throughout the pregnancy.…”
Section: Introductionmentioning
confidence: 99%